Eradication of Neglected Surgical Diseases in Kenya: A Study Protocol - Jaymie, Henry; Mwai, Patrick; Waiguru, Estella; Jani, Pankaj (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: We aim to conduct a county-wide door to door identification, referral, and treatment of Neglected Surgical Diseases (NSDs) as a health systems strengthening activity. Methods: To establish the true prevalence of NSDs and to pilot test an eradication strategy, a single-county door to door census will be conducted in a county in Kenya by community health workers (CHWs) utilizing a mobile app that categorizes six NSDs: obstetric fistula, cleft lip and palate, cataracts, clubfoot, hernia, and neglected injuries. A two-day training workshop on NSD identification was conducted. Prevalence data will be calculated. Identified cases will immediately be referred for treatment to established NGOs who will also train existing health workers in appropriate level district hospitals. Results: Meru County was identified as a pilot study area with a population of 1,517,077 people, 11 administrative sub-counties, and 45 wards. A total of 1,552 CHWs were identified. Demographic data on the number of patients with NSDs, the type of NSD, their contact details, geographical location as well as the contacts of the parent/guardian will be collected by trained research assistants. The data will be fed onto a dashboard that dynamically updates with each NSD identified to aid in tracking cases.